Associations between growth from birth to 18 years, intelligence, and schooling in a Brazilian cohort. Issue 1 (2nd April 2020) - Baptista Menezes, Ana Maria; Oliveira, Paula D; Wehrmeister, Fernando C; Anselmi, Luciana; Gonçalves, Helen; Martorell, Reynaldo; Black, Robert E; Barros, Fernando C; Victora, Cesar G
ABSTRACT: Background: Growth faltering in the first 1000 d is associated with lower human capital among adults. The existence of a second window of opportunity for nutritional interventions during adolescence has been postulated. Objectives: We aimed to verify the associations between growth from birth to 18 y and intelligence and schooling in a cohort. Methods: A total of 5249 hospital-born infants in Pelotas, Brazil, were enrolled during 1993. Follow-up visits to random subsamples took place at 6, 12, and 48 mo and to the full cohort at 11, 15, and 18 y. Weight and length/height were collected in all visits. The Wechsler Adult Intelligence Scale was applied at age 18 y, and primary school completion was recorded. Conditional length/height and conditional BMI were calculated and expressed as z scores according to the WHO Growth Standards. These express the difference between observed and expected size at a given age based on a regression that includes earlier anthropometric measures. Analyses were adjusted for income, parental education, maternal skin color and smoking, and breastfeeding duration. Results: In the adjusted analyses, participants with conditional length ≥1 z score at 1 y had mean intelligence quotient (IQ) scores at 18 y 4.50 points (95% CI: 1.08, 7.92) higher than those with conditional length ≤−1 at 1 y. For height-for-age at 4 y, this difference was equal to 3.70 (95% CI: 0.49, 6.90) IQ points. There were no associations between conditional height at 11, 15, or 18 y and IQ. For the same previously mentioned comparison, the prevalence ratio for less than primary schooling was 1.42 (95% CI: 1.12, 1.80) for conditional height at 1 y. There were no consistent associations with conditional BMI. Conclusions: Our findings show that adolescent growth is not associated with intelligence and schooling, and are consistent with the literature on the associations between intelligence and schooling and early linear growth.